Triiodothyronine stimulates VEGF expression and secretion via steroids and HIF-1α in murine Leydig cells. (4th May 2018) - Dhole, Bodhana; Gupta, Surabhi; Venugopal, Senthil Kumar; Kumar, Anand
ABSTRACT: Leydig cells are the principal steroidogenic cells of the testis. Leydig cells also secrete a number of growth factors including vascular endothelial growth factor (VEGF) which has been shown to regulate both testicular steroidogenesis and spermatogenesis. The thyroid hormone, T3, is known to stimulate steroidogenesis in Leydig cells. T3 has also been shown to stimulate VEGF production in a variety of cell lines. However, studies regarding the effect of T3 on VEGF synthesis and secretion by the Leydig cells were lacking. Therefore, we investigated the effect of T3 on VEGF synthesis and secretion in a mouse Leydig tumour cell line, MLTC-1. The effect of T3 was compared with that of LH/cAMP and hypoxia, two known stimulators of Leydig cell functions. The cells were treated with T3, 8-Br-cAMP (a cAMP analogue), or CoCl2 (a hypoxia mimetic) and VEGF secreted in the cell supernatant was measured using ELISA. The mRNA levels of VEGF were measured by quantitative RT-PCR. In the MLTC-1 cells, T3, 8-Br-cAMP, and CoCl2 stimulated VEGF mRNA levels and the protein secretion. T3 also increased steroid secretion as well as HIF-1α protein levels, two well-established upstream regulators of VEGF. Inhibitors of steroidogenesis as well as HIF-1α resulted in inhibition of T3 -stimulated VEGF secretion by the MLTC-1 cells. This suggested a mediatory role of steroids and HIF-1α protein in T3 -stimulated VEGF secretion by MLTC-1 cells. The mediation by steroids and HIF-1α were independent of each other. Abbreviations : 8-Br-cAMP: 8-bromo – 3ʹ, 5ʹ cyclic adenosine monophosphate; CoCl2 : cobalt chloride; HIF-1α: hypoxia inducible factor −1α; LH: luteinizing hormone; T3 : 3, 5, 3ʹ-L-triiodothyronine; VEGF: vascular endothelial growth factor